Riesgo del periodista en tiempos de conflicto. Caso asesinato de Gerardo Delgado, Ecuador 2022 - Ramírez Cornejo, Steven Julio (2023)
This research analyzes the risks faced by journalists in conflict zones and how this can affect press freedom and democracy, through the case of Gerardo Delgado's murder in Ecuador in 2022. The specific objectives were to identify the risks faced by journalists in conflict zones, analyze the causes and consequences of Delgado's murder, and evaluate measures to reduce risks to journalists and safeguard press freedom in these areas. The results of the research show that journalists working in conflict zones face serious risks, including physical violence, threats, and harassment, which can limit their ability to report with freedom and objectivity. Furthermore, violence against journalists in these areas not only affects them but also society as a whole, compromising democracy. It is concluded that measures must be taken to reduce risks to journalists in conflict zones, including physical and legal protection, training, and financial support. Additionally, measures must be implemented to ensure press freedom in these areas, such as promoting transparency and access to information, regulating the media, and providing legal protection for journalistic work.